Reaksi tekanan terhadap kesihatan mental juvana - Mahadir Ahmad,; Normah Che DIn,; Fauziah Shaari, (penerbit ukm, 2004)
This study examines the effect of temperament, stress factors, and stress reactions towards mental health of juvenile adolescents. Fifty-five juveniles from a rehabilitation centre were selected between the ages of 15 to 18 years. General Health Questionnaire (GHQ28), Student Life Stress Inventory(SLSI), and Dimensions of Temperament DOTSR-Child (Self) were used. Regression and correlation analysis were carried out. The result showed stress factors, responds to stress and temperament on the whole does not significantly affects mental health of the juvenile adolescents but stress factors alone were found as a significant predictor for depression accounted for 14.6% of the variance. Among the stress factors frustration accounted for 18.1% of the variance that predicts depression. Emotional reactions contribute 10.6% towards anxiety and insomnia. Stress factors have moderate positive correlation with emotional reactions (r = 0.55), low positive correlation with temperament (r = 0.11)and mental health (r = 0.23). Overall stress factors play an important role in influencing reactions towards stress. Temperament does not influence much on juvenile reactions toward stress and their mental health. Frustration is a significant predictor of depression as a result of failure to achieve goals or delay in achieving objectives or loss of important resources.